Monitoring of Pest and Natural Enemies Diversity at The Edge and Central of Corn Crops with Pitfall Traps - Eko Apriliyanto; Arum Asriyanti Suhastyo (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2023)
Efforts to determine the presence and population of pests and natural enemies can be carried out through effective monitoring activities using certain traps. At the beginning of corn growth, plants are still susceptible to plant pests and disease organisms (OPT) on the soil surface. Therefore, pitfall can be used to monitor the insects. Research consisted of two treatments, the location of pitfall traps on the edge and middle of the cornfield. The research area measures 11 x 14 m with 24 pitfalls for each treatment. The pitfall trap was installed using a 220 mL plastic glass buried deep and filled with a detergent solution at a dose of 23 grams in 25 liters of water and left for 24 hours. All insects obtained and identified at the family level and their numbers populations. Data were analyzed using the T-Test. There are seven families whose role as pests are Acrididae, Gryllidae, Carabidae, Agromyzidae, Termitidae, Cicadellidae, and Blattidae. There are four families as natural enemies, namely Libellulidae, Lycosidae, Araneidae, and Formicidae. The percentage of pests and natural enemies on the edge of the field is 33.57% and 66.43%. In addition, the pest percentage in the middle of the cornfield is 28.69%, while natural enemies are 71.31%.